Rock paper incisors : a Skunk and Badger story - Timberlake, Amy (Timberlake, Amy. Skunk and Badger (Series), 2025)
"Badger has a very important article about rocks to finish, but Skunk's cooking, two mischievous young rats, and the looming specter of hibernation keep getting in the way"--